Toll-like Receptor Expression Patterns in the Female Reproductive Tract of Sheep - Zhibo Wang; Jian Zheng; Hua Yang; Xu Feng; Fengzhe Li; Jing Pang; Xiaolei Yao; Feng Wang; Yanli Zhang (Animals, 2025)
Toll-like receptors (TLRs) play crucial roles in innate immunity, but their function in reproduction remains poorly understood. This study investigated the expression patterns and localization of TLR1-9 in the reproductive system of Hu sheep and their potential association with prolificacy. All TLRs were expressed in the oviduct, uterus, and ovary, with TLR6 showing significantly higher expression in the oviduct, while TLR3, TLR6, and TLR7 were predominantly expressed in the ovary. Following this initial screening, we focused on TLR2, TLR6, and TLR7 for detailed analysis. Immunohistochemical analysis revealed that TLR2, TLR6, and TLR7 were localized in the luminal epithelium and circular muscle of the oviduct, the luminal and superficial glandular epithelium of the uterus, and in ovarian follicles at all developmental stages. A comparative analysis between high-prolificacy (HP) and low-prolificacy (LP) Hu sheep demonstrated significantly lower TLR2 expression in the reproductive organs of HP sheep, while TLR6 expression was higher and TLR7 expression was lower in HP ovaries compared to LP ovaries. Notably, TLR7 was observed around apoptotic bodies of granulosa cells, suggesting a potential role in follicular development through the regulation of granulosa cell apoptosis. These findings establish a novel link between innate immunity and reproductive function in sheep, suggesting that TLRs, particularly TLR2, TLR6, and TLR7, may serve dual roles as immune sentinels and reproductive regulators influencing ovine fertility.